1982
DOI: 10.1021/ma00232a006
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of poly(n-butyl acrylate). Photochemical processes in polymeric systems. 8

Abstract: The photochemistry of poly(n-butyl acrylate) (PnBA) has been studied at 77 and 298 K. The principal photoproducts of Norrish type I and II processes have been identified and their quantum yields have been measured. The chemistry of photogenerated radicals has been monitored via ESR spectroscopy. Both Norrish type I and II products are observed at room temperature on excitation at 253.7 nm. Hydrogen abstraction takes place from backbone methylene groups in samples excited at 77 K, while tertiary hydrogen abstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 8 publications
1
25
0
Order By: Relevance
“…The other two b-protons are assumed to be positioned close to the nodal plane of the single electron orbital due to restricted rotation around the C a ÀC b bond. [21][22][23][24] Experimental support for this assignment comes from the broad triplet spectra seen during photolysis of tert-butyl peroxide in the presence of poly(tert-BA) [14] and during polymerization of oligomeric acrylic acid. [22] Broad triplets are also observed for acrylate radicals in polymer films at temperatures below 60 8C.…”
Section: Assignment Of the Epr Bandsmentioning
confidence: 98%
“…The other two b-protons are assumed to be positioned close to the nodal plane of the single electron orbital due to restricted rotation around the C a ÀC b bond. [21][22][23][24] Experimental support for this assignment comes from the broad triplet spectra seen during photolysis of tert-butyl peroxide in the presence of poly(tert-BA) [14] and during polymerization of oligomeric acrylic acid. [22] Broad triplets are also observed for acrylate radicals in polymer films at temperatures below 60 8C.…”
Section: Assignment Of the Epr Bandsmentioning
confidence: 98%
“…[30][31][32][33][34][35][36][37] In addition, some degradation reactions dependent on the wavelength of applied radiation have been shown to occur. [33,34,[38][39][40] Our previous publications clearly demonstrated that degradation mechanisms cannot necessarily be extrapolated from other studies under different conditions. [1,41] The present study follows on from these recent publications, examining the degradation behaviour of pBA and pHEMA under the worst-case conditions likely to be experienced by a surface coating on a roof exposed to the harsh Australian environment.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26]36,40,[42][43][44][45] However, as with pMMA, much of this work involves degradative conditions that are not overly relevant to a surface coating exposed to the harsh Australian climate over long periods of time. Thermal degradation studies on pBA indicate that it undergoes a number of different reactions, forming volatile products such as CO 2 , 1-butene and 1-butanol, [16] as well as the 'unbuttoning' reaction which yields fragments of the monomer molecules [17] (rather than the 'unzipping' reaction seen in pMMA, which results in intact monomer molecules [46][47][48][49] ).…”
Section: Introductionmentioning
confidence: 99%
“…With such hexyl functionalized model precursors, the formation of new hydroxyl endgroups as triggered by UV irradiation could be detected using the methylene signal at 3.65 ppm, which would not be easily possible with hydroxyl‐terminated oCL. The formation of hydroxyl endgroups is again a typical observation for photolysis of ester groups …”
Section: Discussionmentioning
confidence: 99%